Sintaksis Bahasa Indonesia Dan Bahasa Arab: (Studi Analisis Kontrastif Frasa, Klausa dan Kalimat) - Farid, Edi Kurniawan Farid (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2020)
The urgency of contrastive analysis studies, which is a systematic study of language pairs to identify the differences and similarities between the two, cannot be denied. While syntax is a science that studies grammar, where the scope of the study is grammar which discusses the relationship between words in speech, which is the subject of basic language studies, especially in Arabic. In Arabic, the study of syntax is known by nahwu. So syntactically the Arabic discussion includes the arrangement of idlofah, jumlah, and kalam. From the contrastive analysis, the scope of phrases, clauses, and sentences can be intermediaries to facilitate the teaching of Arabic through the similarities and differences that exist in these two languages. In this paper, the author will compare Arabic examples related to syntactic functions, phrases, clauses, and sentences, so as to facilitate the teaching of Arabic through the similarities and differences found in these two languages.